Unlocking the potential: Transformative applications of generative AI in East Kalimantan's educational landscape - Sitinjak, Charli; Ober, Józef; Sakiewicz, Piotr (LPMPP Universitas Negeri Yogyakarta, 2025)
AI systems like ChatGPT are rapidly changing education, giving teachers both new opportunities and new problems to deal with. This study investigates ChatGPT's evolving importance in the educational environment of East Kalimantan, focusing on educators' and practitioners' perceptions of its advantages, constraints, and ethical considerations. A qualitative design was used, incorporating semi-structured interviews with 15 participants (N=15), comprising teachers, administrators, and vocational instructors from various educational tiers. Participants were intentionally recruited through professional networks to ensure a representation of various institutional contexts. Data were gathered from March to May 2024 and examined through reflexive thematic analysis to discern the main themes and interpretive significances. Strict adherence to ethical protocols was maintained, including informed consent, secrecy, and voluntary participation. Nine themes emerged: Catalyst for Innovation, Enhancing Accessibility, Efficiency, and Teacher Support, Threat to Critical Thinking, Ethical Dilemmas, Digital Divide, Balancing Human Interaction, Depersonalization of Education, and Continuous Adaptation. The results show that ChatGPT encourages personalized learning, language inclusion, and efficient teaching, but also raises ethical concerns and exacerbates digital inequalities. Participants stressed the importance of teacher guidance, interpersonal connections, and institutional policies to ensure responsible use. The study finds that for ChatGPT to work well, teachers must continue learning, there must be ethical governance, and the digital infrastructure must be fair. This research, despite its regional limitations and reliance on self-reported data, offers significant insight for policymakers and educators addressing AI integration in evolving educational frameworks.